Development of the Huntington Support App (HD-eHelp study): a human-centered and co-design approach - van Lonkhuizen, Pearl J. C.; Heemskerk, Anne-Wil; Meijer, Eline; van Duijn, Erik; de Bot, Susanne T.; Klempir, Jiri; Landwehrmeyer, G. Bernhard; Mühlbäck, Alzbeta; Hoblyn, Jennifer; Squitieri, Ferdinando; Chavannes, Niels H.; Vegt, Niko J. H.; et al. (Frontiers in Neurology, 2024)
Introduction eHealth seems promising in addressing challenges in the provision of care for Huntington’s disease (HD) across Europe. By harnessing information and communication technologies, eHealth can partially relocate care from specialized centers to the patients’ home, thereby increasing the availability and accessibility of specialty care services beyond regional borders. Previous research on eHealth (development) in HD is however limited, especially when it comes to including eHealth services specifically designed together with HD gene expansion carriers (HDGECs) and their partners to fit their needs and expectations. Methods This article describes the qualitative human-centered design process and first evaluations of the Huntington Support App prototype: a web-app aimed to support the quality of life (QoL) of HDGECs and their partners in Europe. Prospective end-users, i.e., HDGECs, their partners, and healthcare providers (HCPs), from different countries were involved throughout the development process. Through interviews, we captured people’s experiences with the disease, quality of life (QoL), and eHealth. We translated their stories into design directions that were further co-designed and subsequently evaluated with the user groups. Results The resulting prototype centralizes clear and reliable information on the disease, HD-related news and events, as well as direct contact possibilities with HCPs via an online walk-in hour or by scheduling an appointment. The app’s prototype was positively received and rated as (very) appealing, pleasant, easy to use and helpful by both HDGECs and partners. Discussion By involving end-users in every step, we developed a healthcare app that meets relevant needs of individuals affected by HD and therefore may lead to high adoption and retention rates. As a result, the app provides low-threshold access to reliable information and specialized care for HD in Europe. A description of the Huntington Support App as well as implications for further development of the app’s prototype are provided.